Perceived factors affecting students' academic performance in Nigerian Universities - E. Glory Okoedion; Ugo C. Okolie; Idongesit D. Udom (Firenze University Press, 2019)
The academic performance of students' has been subject of discourse among social scientists from a wide range of disciplines in the last two decades. But unfortunately, very insufficient number of studies in this area has been conducted in Nigeria. This study was undertaken to fill this obvious research gap. Possible factors affecting students' academic performance in Nigerian universities were examined in this study. They were grouped into student related factors, lecturer related factors, institutional related factors and home related factors. A descriptive method was adopted and data was collected via a survey of 400 respondents selected by means of stratified random sampling technique to ensure a balanced representation of age and gender. Data collected were analyzed using percentages, means, t-test and multiple regression analysis with the aid of Statistical Package for Social Science (SPSS) version 21. The findings indicated that the major factors affecting students' academic performance in Nigerian universities are student, lecturer and institutional related factors. The study also revealed a significant joint contribution of student, lecturer, institutional and home related factors on poor academic performance of students in Nigerian universities. Requisite conclusion and recommendations were provided in the light of the empirical findings.